Data for Semantically enhanced version of a research article from PLoS Neglected Tropical Diseases - Shotton, D (University of Oxford, 2011)
Semantic enhancement: The semantic enhancements to the original PLoS NTD paper by Reis et al (2008) were created by David Shotton, Alistair Miles, Graham Klyne and Katie Portwin, Image Bioinformatics Research Group, Department of Zoology, University of Oxford.